2004
DOI: 10.1002/cncr.20382
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of the first Italian Association of Pediatric Hematology and Oncology protocol for the treatment of pediatric B-cell non-Hodgkin lymphoma (AIEOP LNH92)

Abstract: The authors thank Dr. Gloria Tridello for her assistance with the statistical analysis and Ms. Ilaria Zecchini for her assistance with data management.The following institutions and investigators participated in the current

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 17 publications
(23 reference statements)
4
37
0
Order By: Relevance
“…The intent of the AIEOP LNH-97 protocol, i.e. to increase the cure rate while decreasing the treatment-related toxicity, was fully achieved, thus proving superiority compared to our previous LNH-92 trial (Pillon et al, 2004). The toxic death rate was reduced from 3Á5% to 1Á4%, with only 0Á4% of patients dying of toxicity during the initial phases of chemotherapy.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The intent of the AIEOP LNH-97 protocol, i.e. to increase the cure rate while decreasing the treatment-related toxicity, was fully achieved, thus proving superiority compared to our previous LNH-92 trial (Pillon et al, 2004). The toxic death rate was reduced from 3Á5% to 1Á4%, with only 0Á4% of patients dying of toxicity during the initial phases of chemotherapy.…”
Section: Discussionmentioning
confidence: 69%
“…That study obtained final results [10-year overall survival (OS) of 89% and event-free survival (EFS) of 82%] comparable with contemporary international trials, but showed a high incidence of early toxicity and deaths (Pillon et al, 2004). The subsequent AIEOP LNH-97 protocol was developed aiming at reducing toxic deaths while improving EFS.…”
mentioning
confidence: 77%
“…19,[31][32][33] Data on the additional impact of sex within the adolescent age group are lacking. Recently presented molecular data on somatic mutations in the variable region of rearranged immunoglobulin genes of 54 molecular Burkitt's lymphoma indicated two gene rearrangements occurring almost exclusively in pediatric patients o14 years of age, providing evidence for an antigen-driven selection, which might differ between pediatric and adult Burkitt's lymphoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…The randomized, double-blind and multicenter prospective study conducted by Pillon et al [10] showed that the preventive use of amoxicillin/clavulanic acid in 173 pediatric patients with acute leukemia and lymphoma reduced neutropenic fever and infection by 12%. In particular, these patients did not receive any stimulating factors, but no significant difference was found between the prophylactic and control groups [18].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study conducted by the Nordic Society of Pediatric Hematology and Oncology (NOPHO) [10] reported that 10% of pediatric patients died mainly from infections after the 15th day of chemotherapy, and the NOPHO suggested the use of prophylactic antibiotic treatment and also emphasized the necessity of studying the benefits of combining the use of prophylactic antibiotics [11]. Various clinical studies and meta-analyses have demonstrated that preventive use of fluoroquinolone antibiotics effectively reduce bacterial infection rate, infectious fever and overall mortality rate [12,13,14].…”
Section: Introductionmentioning
confidence: 99%